2015
DOI: 10.1007/s12639-015-0643-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two hydatid cyst antigens on the growth of melanoma cancer in C57/black mice

Abstract: Hydatid cyst is the larval stage of Echinococcus granulosus. In previous studies inhibitory effect of this parasite on cancer cell growth in culture medium has been shown. In this study effect of hydatid cyst antigens on tumor growth in experimental animals has been investigated. Two antigens of hydatid cyst including protoscolices excretory secretory antigen and hydatid fluid absorbed on alum as adjuvant were injected to two groups of C57/black mice as case groups. Control groups were injected with only salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Median survival time for HCC patients was 6 month (1-17). However, that was 8 month (3-90) for patients with both conditions, which was closely associated with tumor size, location, TMN stage and hydatid size, location, classification [28,29] and our results were highly accorded with previous studies. Importantly, four patients underwent surgical intervention and median survival time for them was 17 month (3-68), which was significantly longer than reported average level by some researchers that the median survival time for advanced HCC patients was only 3-5 month [5].…”
Section: Discussionsupporting
confidence: 91%
“…Median survival time for HCC patients was 6 month (1-17). However, that was 8 month (3-90) for patients with both conditions, which was closely associated with tumor size, location, TMN stage and hydatid size, location, classification [28,29] and our results were highly accorded with previous studies. Importantly, four patients underwent surgical intervention and median survival time for them was 17 month (3-68), which was significantly longer than reported average level by some researchers that the median survival time for advanced HCC patients was only 3-5 month [5].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard it has also been shown that T. gondii is able to generate therapeutic antitumor immunity against ovarian cancer (8). Besides T. gondii, anticancer activities of other parasites including Trypanpsoma cruzi (9), malaria parasite (10) and hydatid cyst [larval stage of Echinococcus granulosus (E. granulosus)] (11)(12)(13) have also been reported. The mechanisms underlying the anticancer effects of parasites are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma cells were purchased from Pastor Institute and cultured in RPMI medium enriched with fetal bovine serum. The cells were then harvested for injection to mice as we did before [5].…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study, it has been shown that in patients with hydatid cyst, incidence of different cancers was much lower than what exist in normal population [2]. Also the effect of different hydatid cyst antigens on inhi-H bition of the melanoma cancer growth has been reported in animal model [3][4][5] and in cell culture medium [6][7][8].…”
Section: Introductionmentioning
confidence: 99%